Poor fisheries data, many fishers, and increasing tourism development: Interdisciplinary views on past and current small-scale fisheries exploitation on Holbox Island. (February 2019) - Rubio-Cisneros, Nadia T.; Moreno-Báez, Marcia; Glover, Jeffrey; Rissolo, Dominique; Sáenz-Arroyo, Andrea; Götz, Christöpher; Salas, Silvia; Andrews, Anthony; Marín, Gustavo; Morales-Ojeda, Sara; Antele, Francisca; Herrera-Silveira, Jorge
Abstract: Holbox Island is a contemporary hotspot for global tourism. Here, long-term coastal exploitation and increasing anthropogenic activities threaten coastal habitats and resources. The impact of these activities is exacerbated by the lack of a management plan for the past 24 years, until October 2018. An interdisciplinary approach that integrates fishers' traditional knowledge was used to determine how small-scale fisheries (SSF) exploitation contributed to the decline of resources over time. Open interviews with community members and surveys of fishers' perspectives on fisheries overexploitation and practices as well as knowledge of fishing sites were collected. Over one hundred fishing sites were documented that were once very productive. Furthermore, over 40 species were highly fished ( e.g., Carcharhinidae, Shpyrnidae, Pristidae, Cheloniidae) over the past 50 years. Survey results allowed for the construction of maps with baseline information of coastal exploitation. Additional data from archaeozoological remains (n= 545) of aquatic fauna identified 33 families of exploited taxa, of which finfish ( e.g., Haemulidaea, Ariidae, Serranidae), sharks ( e.g., Carcharhinidae), and sea turtles were the most abundant. Fishers and literature sources (n= 50) document Holbox's contemporary issues, including overfishing, illegal fishing, and accelerated tourism development. These types of data (fishers' perspectives, interdisciplinary literature, and archaeozoological data) were combined using historical ecology techniques and geospatial tools to obtain novel baseline information on SSF exploitation. This information is essential for conservation managers and scientists to meet the management needs of Holbox's natural and social capital, which can assure the future provision of coastal ecosystem services to humans. Graphical abstract: Holbox Island is a contemporary hotspot for global tourism. Here, long-term coastal exploitation and increasing anthropogenic activities threaten coastal habitats and resources. The impact of these activities is exacerbated by the lack of a management plan for the region. An interdisciplinary approach that integrates fishers' traditional knowledge was used to determine how small-scale fisheries (SSF) exploitation contributed to the decline of resources over time. Open interviews with community members and surveys of fishers' perspectives on fisheries overexploitation and practices as well as knowledge of fishing sites were collected. Over one hundred fishing sites were documented that were once very productive. Furthermore over 40 species were highly fished (e.g., Carcharhinidae, Shpyrnidae, Pristidae, Cheloniidae) over the past 50 years. Survey results allowed for the construction of maps with baseline information of coastal exploitation. Additional data from archaeozoological remains (n= 545) of aquatic fauna identified 33 families of exploited taxa, of which fmfish (e.g., Haemulidaea, Ariidae, Serranidae), sharks (e.g., Carcharhinidae), and sea turtles were the most abundant. Fishers and literature sources (n= 50) document Holbox's contemporary issues, including overfishing, illegal fishing, and accelerated tourism development. These types of data (fishers' perspectives, interdisciplinary literature, and archaeozoological data) were combined using historical ecology techniques and geospatial tools to obtain novel baseline information on SSF exploitation. This information is essential for conservation managers and scientists to meet the management needs of Holbox's natural and social capital, which can assure the future provision of coastal ecosystem services to humans.fx1 Highlights : Holbox Island (HI), is a hotspot spot for international tourism which is leading to increasing threats for biodiversity and habitat conservation. Combining fishers' traditional knowledge, interdisciplinary literature, and archaeozoological data; spatial and qualitative baseline information on small-scale fisheries exploitation at HI is provided and can help develop management actions. Finfish, sharks, and sea turtles, were the most abundant exploited taxa in archaeozoological remains. For the contemporary history of HI over 40 highly fished species (e.g. Carcharhinidae, Pristidae) were documented in the past 40 years. Fishers' traditional knowledge documented over 100 fishing sites which allowed the construction of informative maps about small-scale fisheries exploitation. Fishers' and literature sources report increasing fishing effort, overfishing, illegal fishing and social conflicts related to the use of coastal resources.